Transient wave-leak interaction analysis for improved leak detection in viscoelastic pipelines. (28th February 2023) - Zhang, Ying; Duan, Huan-Feng; Keramat, Alireza; Pan, Bin; Meniconi, Silvia; Brunone, Bruno; Lee, Pedro J.
Highlights: The formulation of transient wave-leak-viscoelasticity interactions is developed and scrutinized. An improved leak detection method in viscoelastic pipelines is proposed based on the presented analytical results. The analytical expressions and the leak detection method are validated by numerical and laboratory experiments. Systematic analysis and discussion is conducted on the influences of different factors and application to the leak detection. Abstract: Transient wave reflection methods (TWRMs) have exhibited favorable capability in leak detection for elastic pipelines, but applications have demonstrated their relatively low accuracy for viscoelastic pipelines. This paper investigates the transient wave behaviour, the principal tenet for leak detection by TWRMs, in a leaky viscoelastic pipeline to understand the mechanism of wave modification by leaks and viscoelasticity. Based on the correspondence principle, this research derives analytical formulations of the leak-induced wave reflection and phase difference at any measurement point in a viscoelastic pipe. According to the measured reflection coefficient, an optimization algorithm is further developed to detect the leak. The methodologies are then assessed and discussed through sinusoidal and sigmoid perturbations in numerical and laboratory tests. The extensive analyses indicate that measurement distance and leak ratio affect the magnitude of the reflected wave, yet, the wave phase shift is relatively independent of the leak ratio for practical applications.